Experimental study on transverse reinforcements of reinforced concrete-filled steel tubular column. (15th November 2019) - Xiamuxi, Alifujiang; Maimaitimin, Maimaitiyasen; Liu, Xiaorui; Hasegawa, Akira
Highlights: Lateral hoops of axially loaded circular section R-CFST column were studied. Before-peak loading performances are not relevant to the pattern and spacing of hoops. Large spaced hoops are suggested for a time- and work-saving construction process. Several strength prediction methods were investigated. New equation was proposed to predict the strength of axially loaded R-CFST column. Abstract: Experimental investigations were conducted to understand the effects of transverse reinforcements on the overall performance of a circular section reinforced concrete-filled steel tubular (R-CFST) column subjected to axial loads. Compression tests were then conducted with 34 column specimens divided into three test series. In these tests, the transverse reinforcements were configured in spiral and flat hoop patterns, and the flat hoop patterns were configured with tightly and loosely arranged longitudinal spacing. Additional test variables included the specimen size, strength of materials, and ratio of longitudinal reinforcements. Based on the experimental results, a comprehensive analysis was performed on the load transfer performance, ductility, confinement, composite effect, and failure mode. The analysis results demonstrated the following: the before-peak loading performance and ultimate load-bearing capacity are not relevant to the hoop patterns; differences in spacing of the flat hoops will not cause significant changes in the mechanical performance, and thus larger spacing is recommended to obtain a time- and work-saving construction process; compared to flat hoops, spiral hoops will improve the ductility and post-peak loading performance further, and thus, the spiral hoop is recommended when the ductility or seismic performance is the main concern. Moreover, prediction methods for the ultimate load-bearing capacity of the member were investigated, and a new equation was proposed.